French children under the Allied bombs, 1940-45 : An oral history - Dodd, Lindsey (Book collections on Project MUSE., 2016)
Children under the Allied bombs in France provides a unique perspective on the Allied bombing of France during the Second World War which killed around 57,000 French civilians. Using oral history as well as archival research, it provides an insight into children's wartime lives in which bombing often featured prominently, even though it has slipped out of French collective memory. How prepared were the French for this aerial onslaught? What was it like to be bombed? And how did people understand why their 'friends' across the Channel were attacking them? Divided into three parts dealing with expectations, experiences and explanations of bombing, this book considers the child's view of wartime violence, analysing resilience, understanding and trauma. It contributes significantly to scholarship on civilian life in Occupied France, and will appeal to students, academics and general readers interested in the history of Vichy France, oral history and the experiences of children in war.--